(untitled) (KULT_online, 2009)
This new volume in literary studies looks back upon international contemporary literature from 1995-2005. One the one hand, it is a literary studies investigation of the themes, transformations, and writing techniques that prevailed at the turn of the millennium; on the other hand, it is a study of book market dynamics from an industry perspective. This dual enquiry provides a panoramic overview of contemporary literature and its recent development. The topics of analysis range from political phenomena like terrorism and globalisation, with references to such recent historical events as 9/11, to the typical working conditions of authors and editors, and alltogether provide comprehensive insights into the industry’s movers and shakers.